Tindak Pidana Korupsi Bidang Pertanahan Terhadap Program Pendaftaran Tanah Sistematis Lengkap (PTSL) - Sudarmanto, Kukuh; Arifin, Zaenal; Tatara, Tirsa (Universitas Semarang, 2023)
The purpose of the research conducted is to find out and analyze the juridical study of corruption crimes in the implementation of the Complete Systematic Land Registration (PTSL) program and the ideal concept pursued by the government as an anti-corruption effort to be applied in the implementation of the Complete Systematic Land Registration (PTSL) program in the future. This research uses sociological juridical legal researc.The results of the study can be concluded that corruption crimes in PTSL begin with the identification of the causes of corruption crimes. In terms of law enforcement, it is related to efforts to prevent and eradicate corruption, whether or not law enforcement is successful depends on the components of the legal structure, legal substance, and legal culture.Law enforcement is described in several stages including pre-adjudication with the cooperation of the Pungli Saber Team which continues the process of investigating and investigating suspected perpetrators of corruption crimes by the police by including at least 2 (two) pieces of evidence, after the minutes of the results of the complete investigation (P21) then proceed to the prosecutor's office.The ideal concept pursued by the government in the future as an effort to implement an anti-corruption program consists of external and internal concepts, in addition to that government steps are needed to evaluate, update, and/or change.The suggestion this research is that it is hoped that the first land registration program based on PTSL which is carried out en masse which is intended for all economic groups can be carried out smoothly for the orderly order of national land law to ensure legal certainty and legal protection for owners of rights to a plot of land. Tujuan dalam penelitian yang dilakukan untuk mengetahui dan menganalisa kajian yuridis tindak pidana korupsi) dan penanganan pencegahan pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) Penelitian ini menggunakan penelitian hukum yuridis sosiologis. Hasil penelitian dapat disimpulkan bahwa tindak pidana korupsi dalam PTSL dimulai dengan adanya identifikasi penyebab terjadi tindak pidana korupsi. Pelaksanaan PTSL sendri banyak dtemukan unsur tindak pidana koruspi seperti adanya pungutan liar dan gratifikasi. Salah satu upaya pencegahan tindak pidan korupsi dalam PTSL melalui kerja sama dengan Tim Saber Pungli. Konsep ideal yang ditempuh pemerintah pada masa yang akan datang sebagai upaya program anti korupsi terdiri dari konsep eksternal dan internal, selain itu diperlukan langkah pemerintah untuk melakukan evaluasi, pembaharuan, dan/atau perubahan. Saran yang digunakan oleh penlitian ini adalah diharapkan progam pendaftaran tanah pertama kali berdasarkan PTSL yang dilakukan secara massal yang diperuntukkan kepada semua golongan ekonomi dapat terlaksana dengan lancar demi tertibnya hukum pertanahan nasional guna menjamin kepastian hukum dan perlindungan hukum bagi pemilik hak atas suatu bidang tanah.